Thiol group-containing polyether polymer, epoxy resin-containing composition, and curing agent for epoxy resin
By designing a polyether polymer containing thiol group, ensuring that it maintains low viscosity and excellent operability when increasing the additive amount, the problem of rising viscosity of existing polythiol-based curing agents is solved, and is suitable for the application of epoxy adhesives.
Patent Information
- Application Number
- CN202380063368.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-06
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-11
AI Technical Summary
When the existing polythiol-based curing agent increases the viscosity of the additive amount, resulting in deterioration of operability, making it difficult to maintain low viscosity and excellent operability.
By designing a thiol-containing polyether polymer, the main chain has a specific polyether part and structural unit, and the ratio of the peak area corresponding to the -SH structural unit to the peak area corresponding to the -Sx- structural unit is more than 7.0 to control viscosity and operability.
It achieves low viscosity and excellent operability when increasing the additive dose, and is suitable for the application of epoxy adhesives.
Smart Images

Figure CN119816541A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polyether polymer containing a thiol group, a composition containing an epoxy resin and a curing agent for the epoxy resin. Background Art
[0002] Cured products containing epoxy resins have good adhesion, chemical resistance, low shrinkage and excellent physical properties, and have been widely used as coatings, adhesives, etc.
[0003] Among them, epoxy adhesives have good adhesion and chemical resistance. As a curing agent for epoxy adhesives, polythiol compounds are used when rapid curing and high bonding strength are required. As a curing agent for epoxy adhesives, polythiol compounds cure quickly compared to other epoxy curing agents.
[0004] As compounds capable of rapidly reacting a thiol group with an epoxy group, a large number of compounds having no polysulfide skeleton in the main chain and having a thiol group at the terminal have been reported (for example, see Patent Document 1).
[0005] Among them, as a curing agent for epoxy resins that is both economical and safe, compounds having a polyether skeleton in the main chain and having three or more thiol groups in each molecule are widely available on the market. As compounds having a polyether skeleton in the main chain and having three or more thiol groups in each molecule, for example, "Polythiole QE-340M" manufactured by Toray Fine Chemicals (Strain) and "GPM-800" manufactured by Huntsman can be cited. Usually, these polythiol curing agents are used by mixing epoxy resins with tertiary amines as curing accelerators.
[0006] For epoxy adhesives using a compound having a polyether skeleton in the main chain and 3 or more thiol groups per molecule as a polythiol curing agent, additives are added to impart various properties such as heat resistance and chemical resistance. However, increasing the amount of additives to impart properties increases the viscosity of the adhesive and deteriorates the workability.
[0007] Therefore, in order to improve the performance of epoxy adhesives using conventional polythiol curing agents, an adhesive that can maintain the conventional viscosity even when the amount of additives is increased is required.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 8-269203 Summary of the invention
[0011] Problems to be solved by the invention
[0012] An object of the present invention is to provide a thiol group-containing polyether polymer which has a lower viscosity than epoxy adhesives using conventional polythiol curing agents, is excellent in workability, and can maintain the low viscosity of the epoxy adhesive even when the amount of additives is increased.
[0013] Means of solving the problem
[0014] The present inventors have found that, as a polythiol curing agent that improves the workability of an adhesive and can maintain the same viscosity and workability as before even when the amount of additives is increased, they have focused on -S which contributes to the viscosity increase of the polythiol compound. x -key quantity, conducted intensive research and resulted in the present invention.
[0015] The present invention is a thiol group-containing polyether polymer, wherein the main chain thereof has a polyether portion represented by the following general formula (1) and a structural unit represented by the following general formula (2), and the terminal has a structural unit represented by the following general formula (3), and 13 In the structural analysis by CNMR measurement, the peak area corresponding to the structural unit of -SH is relative to that of -S x The ratio of the peak areas corresponding to the structural units of -[-SH] / [-S x -] is 7.0 or above.
[0016]
[0017] In formula (1), R 1 It is a residue obtained by removing hydrogen atoms from a polyamine or polyol having 10 or less carbon atoms, R 2 is an alkylene group having 2 to 6 carbon atoms, n is an integer of 1 to 200, and m is an integer of 2 to 8.
[0018]
[0019] In formula (2), S x represents one or two or more consecutive sulfur atoms, x is an integer of 1-5, and l is an integer of 0-10.
[0020]
[0021] In formula (3), l is an integer from 0 to 10.
[0022] The present invention is also an epoxy resin-containing composition comprising 100 to 600 parts by mass of the epoxy resin based on 100 parts by mass of the thiol-containing polyether polymer of the present invention.
[0023] The present invention also provides a curing agent for an epoxy resin, comprising the thiol group-containing polyether polymer of the present invention.
[0024] Effects of the Invention
[0025] According to the thiol group-containing polyether polymer of the present invention, an epoxy adhesive can be provided which, when used as a curing agent for epoxy resin, has a lower viscosity than epoxy adhesives using conventional polythiol curing agents, is excellent in workability, and can maintain a low viscosity even when the amount of additives is increased. DETAILED DESCRIPTION
[0026] The thiol group-containing polyether polymer of the present invention will be described in detail below.
[0027] The thiol group-containing polyether polymer of the present invention has a polyether portion represented by the following general formula (1) in its main chain.
[0028]
[0029] In formula (1), R 1 It is a residue after removing m hydrogen atoms from a polyamine or polyol having a carbon number of 10 or less. Examples of the polyamine or polyol include glycerol, trimethylolpropane, trimethylolethane, hexanetriol, diglycerol, pentaerythritol, triethanolamine, ethylenediamine, sucrose, and the like. These polyamines and polyols may be used alone or in combination. Among the polyols, glycerol, trimethylolpropane, and trimethylolethane are particularly preferred.
[0030] In formula (1), R 2 It is an alkylene group having 2 to 6 carbon atoms, preferably 2 to 4 carbon atoms. Examples of the alkylene group include ethylene, n-propylene, isopropylene, n-butylene, isobutylene, pentylene, and hexylene.
[0031] In formula (1), n is an integer of 1 to 200, preferably 1 to 100.
[0032] In the formula (1), m is an integer of 2 to 8, preferably 2 to 5.
[0033] The thiol group-containing polyether polymer of the present invention preferably contains a structural unit represented by the following general formula (2) in the main chain.
[0034]
[0035] In formula (2), S x represents one or two or more consecutive sulfur atoms, x is an integer of 1-5, and l is an integer of 0-10.
[0036] Furthermore, the thiol group-containing polyether polymer of the present invention has a structural unit represented by the following general formula (3) at the terminal.
[0037]
[0038] In formula (3), l is an integer from 0 to 10.
[0039] The thiol group-containing polyether polymer of the present invention can be obtained by reacting a halogen-terminated polyether polymer with a hydrogen sulfide metal salt.
[0040] The halogen-terminated polyether polymer has a polyether moiety represented by the above-mentioned general formula (1) in the main chain and a structure represented by the following general formula (4) at the terminal.
[0041]
[0042] In formula (4), Y is a halogen atom, and l is an integer of 0-10.
[0043] The above-mentioned polyol is represented by the following general formula (5).
[0044]
[0045] R in formula (5) 1 , R 2 The details of , n and m are the same as those in formula (1).
[0046] The halogen-terminated polyether polymer can be obtained by adding an epihalohydrin to the hydroxyl groups of a polyol having a polyether moiety in the main chain and having two or more hydroxyl groups at the terminals.
[0047] As the above-mentioned polyol, for example, polyols obtained by adding ethylene oxide, propylene oxide, tetrahydrofuran, etc. to polyamines or polyols can be cited. As polyamines or polyols, for example, glycerol, trimethylolpropane, trimethylolethane, hexanetriol, triethanolamine, diglycerol, pentaerythritol, ethylenediamine, sucrose, etc. can be cited. These polyamines and polyols can be used alone or in combination. Among the above-mentioned polyols, polypropylene glycol obtained by adding propylene oxide to glycerol, trimethylolpropane, or trimethylolethane is particularly preferred.
[0048] The molecular weight of the polyol is preferably 200 to 10,000, more preferably 200 to 3,000.
[0049] As the epihalohydrin, epibromohydrin and epichlorohydrin are preferred, and epichlorohydrin is more preferred.
[0050] The usage amount of above-mentioned epihalohydrin is preferably more than 1.0mol times and below 1.5mol times relative to the hydroxyl of above-mentioned polyvalent alcohol.By being set to more than 1.0mol times by this usage amount, can prevent the hydroxyl of polyvalent alcohol from remaining.In addition, by making this usage amount be below 1.5mol times, more preferably below 1.30mol times, can prevent epihalohydrin from remaining.
[0051] By reacting the hydrogen sulfide metal salt, the structures represented by the general formula (2) and the general formula (3) of the thiol group-containing polyether polymer are generated from the structure represented by the general formula (4) of the halogen-terminated polyether polymer.
[0052] Examples of the hydrogen sulfide metal salt include potassium hydrogen sulfide, sodium hydrogen sulfide, lithium hydrogen sulfide, cesium hydrogen sulfide, and rubidium hydrogen sulfide. Among them, sodium hydrogen sulfide is preferred as the hydrogen sulfide metal salt.
[0053] The amount of the hydrogen sulfide metal salt used is preferably 1.0 to 5.0 mol times, more preferably 1.1 to 1.5 mol times, relative to the molar amount of halogen in the terminal halogenated polyether polymer. By setting the amount of the hydrogen sulfide metal salt used within the above range, the halogen content in the thiol group-containing polyether polymer can be reduced to the required range described below.
[0054] In the use of electronic materials, it is required that the components of products, parts and raw materials do not contain halogens or halogen compounds. The international standards IEC (International Electrotechnical Commission) 61249-2-21, the US IPC (International Electrical and Computer Association) 4101B, and the Japanese Electronics and Computers Association (JPCA) define the threshold value of halogen-free, requiring the chlorine (Cl) content to be less than 0.09 mass% (900ppm).
[0055] The above-mentioned hydrogen sulfide metal salt can also be used in an aqueous solution, and the concentration of the hydrogen sulfide metal salt in the aqueous solution is preferably 25 mass % or more, more preferably 32 mass % or more, and further preferably 40 mass % or more. In addition, the concentration is preferably 70 mass % or less.
[0056] When the above-mentioned hydrogen sulfide metal salt is reacted with the above-mentioned terminal halogenated polyether polymer, a solvent may be used. Examples of the above-mentioned solvent include alcohols such as methanol, ethanol, propanol, and butanol, ketones such as methyl ethyl ketone and methyl isobutyl ketone, esters such as ethyl acetate and butyl acetate, sulfoxides such as dimethyl sulfoxide, nitriles such as acetonitrile, amines such as pyridine, amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone, and water. Among them, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and water are particularly preferred.
[0057] The amount of the solvent used is preferably 0.2 to 5.0 times by mass, more preferably 1.0 to 3.0 times by mass, based on the mass of the halogen-terminated polyether polymer.
[0058] When the above-mentioned terminal halogenated polyether polymer is reacted with the above-mentioned hydrogen sulfide metal salt, a catalyst can be used. If a catalyst is used, the reaction rate can be increased and the reaction is completed quickly. As the above-mentioned catalyst, for example, phase transfer catalysts such as tetrabutylammonium chloride (TBAC), tetrabutylammonium bromide (TBAB), tetrabutylammonium hydrogen sulfate (TBAHS), tributylmethylammonium chloride (MTBAC), benzyltrimethylammonium chloride (BTMAC), benzyltriethylammonium chloride (BTEAC), methyltrioctylammonium chloride (MTOAC), tetrabutylphosphonium bromide (TBPB) can be cited. Among them, TBAB and MTBAC are preferred.
[0059] The amount of the catalyst used is preferably 0.005 to 0.2 mol times, more preferably 0.01 to 0.1 mol times, the molar amount of the halogen in the terminally halogenated polyether polymer.
[0060] Examples of the atmosphere in the reaction system when reacting the hydrogen sulfide metal salt with the terminal halogenated polyether polymer include inert gases such as air, nitrogen and helium, and hydrogen sulfide. Among them, hydrogen sulfide is preferred because it has the effect of reducing the viscosity of the obtained thiol group-containing polyether polymer.
[0061] As a method for introducing the hydrogen sulfide, by-produced hydrogen sulfide may be sealed in a sealed container for use, or may be introduced from outside the system using a hydrogen sulfide gas cylinder or the like.
[0062] In addition, the hydrogen sulfide atmosphere can also be formed by a neutralization reaction between an acid and the above-mentioned hydrogen sulfide metal salt. Examples of the acid used in this case include organic carboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, citric acid, and lactic acid, organic sulfonic acids such as methanesulfonic acid and p-toluenesulfonic acid, and inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid. The amount of the acid used can be set according to the internal pressure of the above-mentioned closed container.
[0063] The gauge pressure in the sealed container is preferably 0 to 5.0 MPa, more preferably 0.1 to 3.0 MPa, and even more preferably 0.1 to 2.0 MPa. By setting the gauge pressure during the reaction within the above range, -S x -The increase of bonds reduces viscosity.
[0064] The reaction temperature when the metal hydrogen sulfide salt and the terminal halogenated polyether polymer are reacted is preferably 40 to 130° C., more preferably 60 to 100° C. By setting the reaction temperature within the above range, the halogen content in the generated thiol group-containing polyether polymer can be reduced, and the terminal halogenated polyether polymer can be made to have a viscosity that is easy to handle.
[0065] The reaction time when the metal hydrogen sulfide salt reacts with the terminal halogenated polyether polymer is preferably 1 to 20 hours, more preferably 3 to 9 hours. By setting the reaction time within the above range, the halogen content in the generated thiol group-containing polyether polymer can be reduced, thereby ensuring efficient productivity.
[0066] The thiol group-containing polyether polymer of the present invention preferably has a chlorine content of 900 ppm or less as a halogen. When the chlorine content is 900 ppm or less, more preferably 600 ppm or less, and even more preferably 300 ppm or less, the polymer can be suitably used for electronic materials.
[0067] The thiol group-containing polyether polymer of the present invention preferably contains 10% to 18% by mass of thiol groups. By making the thiol group content 10% or more, more preferably 12% or more, the curing speed can be accelerated when used as a curing agent for an epoxy adhesive. In addition, by making the thiol group content 18% or less, more preferably 17% or less, and further preferably 16% or less, the -S x - The bond is suppressed at a low level, suppressing the viscosity from becoming high.
[0068] The polyether polymer containing thiol groups of the present invention is 13 In the structural analysis by CNMR measurement, the peak area corresponding to the structural unit of -SH is relative to that of -S x The ratio of the peak areas corresponding to the structural units of -[-SH] / [-S x It is important that [-SH] / [-S x -] is 7.0 or more, more preferably 8.0 or more, which can suppress the viscosity from increasing. The -Sx- bond of the polythiol compound represents a high molecular weight body generated by a side reaction, which affects the high viscosity. That is, it is considered that if the -Sx- bond of the polythiol compound is large, the viscosity becomes high, and if it is small, the viscosity becomes low. Therefore, it is considered that the thiol group-containing polyether polymer of the present invention can achieve improved operability of the curing agent and increased amount of additives.
[0069] In addition, [-SH] / [-S x -] is preferably 50.0 or less, more preferably 40.0 or less.
[0070] The viscosity of the thiol group-containing polyether polymer of the present invention at 25° C. is preferably 0.1 to 10 Pa·s, more preferably 0.5 to 8 Pa·s, and even more preferably 1 to 7 Pa·s, from the viewpoint of workability during adhesive production and workability as an adhesive.
[0071] The viscosity of the thiol group-containing polyether polymer of the present invention at 5°C is preferably 1 to 70 Pa·s, more preferably 1 to 60 Pa·s, and even more preferably 1 to 50 Pa·s from the viewpoint of workability when producing an adhesive in cold regions and workability as an adhesive.
[0072] The thiol group-containing polyether polymer of the present invention is preferably used as a curing agent for epoxy resin. The thiol group-containing polyether polymer of the present invention can reduce the viscosity without impairing the curing characteristics of the composition containing epoxy resin. In addition, the thiol group-containing polyether polymer of the present invention can increase the amount of additives such as barium sulfate, calcium carbonate, and silicon powder for imparting heat resistance and chemical resistance in the curing agent using the thiol group-containing polyether polymer of the present invention. That is, the curing agent for epoxy resin of the present invention contains the thiol group-containing polyether polymer of the present invention.
[0073] The epoxy resin-containing composition of the present invention contains the thiol group-containing polyether polymer of the present invention and an epoxy resin.
[0074] Examples of the epoxy resin include epoxy resins obtained by adding epichlorohydrin to polyphenols such as bisphenol A, bisphenol F, resorcinol, hydroquinone, catechol, 4,4-dihydroxybiphenyl, and 1,5-hydroxynaphthalene, epoxy resins obtained by adding epichlorohydrin to polyols such as ethylene glycol, propylene glycol, and glycerin, epoxy resins obtained by adding epichlorohydrin to aromatic dicarboxylic acids such as hydroxybenzoic acid and phthalic acid, and polysulfide polymers having an epoxy group at the end (trade names "FLEP-50" and "FLEP-60", both manufactured by Toray Fine Chemicals Co., Ltd.), and those that are liquid at room temperature are preferred.
[0075] In the epoxy resin-containing composition of the present invention, the content of the epoxy resin is preferably 100 to 600 parts by mass, more preferably 100 to 400 parts by mass, and even more preferably 100 to 200 parts by mass, based on 100 parts by mass of the thiol group-containing polyether polymer.
[0076] In the composition containing epoxy resin of the present invention, the above-mentioned thiol group-containing polyether polymer can be dissolved in a solvent. Thus, the coating property of the composition containing epoxy resin can be effectively improved. As a solvent, an alcohol solvent is preferably used. From the perspective of being able to remove the epoxy resin-containing composition by slight heating distillation after being applied to a substrate, etc., alcohols with low boiling points are preferred. In particular, methanol, ethanol, isopropanol, n-butanol, tert-butanol, n-heptanol, n-hexanol, etc. have excellent compatibility with thiol group-containing polyether polymers and are therefore preferred. Among them, methanol and ethanol as small molecules are more preferred.
[0077] The epoxy resin-containing composition of the present invention preferably contains amines.
[0078] The amount of the amines is preferably 1 to 100 parts by mass, more preferably 1 to 60 parts by mass, based on 100 parts by mass of the epoxy resin. Since the content of the amines affects the pot life, the amount used can be set according to the pot life design.
[0079] Examples of the amines include aliphatic diamines such as ethylenediamine, diethylenetriamine, triethylenetetramine, pentaethylenehexamine, trimethylenediamine, hexamethylenediamine, and tetramethylenediamine; aliphatic tertiary amines such as N,N-dimethylpropylamine, N,N,N',N'-tetramethylhexamethylenediamine; alicyclic tertiary amines such as N-methylpiperidine and N,N'-dimethylpiperazine; benzyldimethylamine, dimethylaminomethylphenol, and 2,4,6-tris(dimethylaminomethyl)phenol (EVMP). Aromatic tertiary amines such as "ANCAMINE" K-54 manufactured by Tonik Industries, EHC-30 manufactured by ADEKA Co., Ltd., polyamine epoxy resin adducts manufactured by reacting epoxy resin with excess amine, polyamine-ethylene oxide adducts, polyamine-propylene oxide adducts, cyanoethylated polyamines, diamines having a polysiloxane main chain, or dehydrated condensates obtained by reacting polyamines with phenols and aldehydes, imidazoles such as 2-ethyl-4-methylimidazole, modified polyamines, etc.
[0080] The epoxy resin-containing composition of the present invention preferably has a pot life of 2 to 10 minutes when cured at 23°C and 50% RH. The pot life is determined in accordance with the method for determining the pot life of a multi-component adhesive of JIS K6870 (method 1). Under the conditions of 23°C and 50% RH, a thiol compound and an amine compound are mixed in a prescribed ratio in 10 g of an epoxy resin to prepare a composition containing an epoxy resin. In the present invention, the moment when these three components are mixed is referred to as the curing start moment. A toothpick is placed in the epoxy resin-containing composition, and the time from the curing start moment to the moment when the toothpick does not move even when touched with a finger is defined as the pot life.
[0081] The epoxy resin-containing composition of the present invention preferably has a Shore D hardness of 60 or more based on JIS K7215 and a tensile shear bond strength of 12 MPa or more based on JIS K6850 24 hours after the start of curing when the epoxy resin-containing composition is applied to a thickness of 6.0 mm or more and cured at 23° C. and 50% RH.
[0082] Example
[0083] The present invention is described in detail below by listing Examples and Comparative Examples. In the following Examples, unless otherwise specified, the raw materials used were common reagents purchased from reagent manufacturers. The following apparatus and method were used for analysis.
[0084] [Measurement method]
[0085] (1) [-SH] / [-S x -]
[0086] Using a nuclear magnetic resonance device (ECZ-600R manufactured by JEOL Resonance Co., Ltd.) 13 CNMR analysis was performed to analyze the structure and the peak area of the structural unit of [-SH] was obtained relative to that of [-S x -] is the ratio of the peak areas of the structural units.
[0087] (2) Viscosity
[0088] The viscosity of the sample at 25°C and 5°C was measured using a viscometer (U-EII manufactured by Toki Sangyo).
[0089] (3) Thiol content
[0090] The weighed sample was dissolved in a mixed solution of toluene and pyridine, and after adding a potassium iodide aqueous solution, titration was performed using an iodine standard solution to determine the content of the thiol group.
[0091] (4) Chlorine content
[0092] The content of chlorine contained in the thiol group-containing polyether polymer was measured using an elemental analyzer (NSX-2100 manufactured by Mitsubishi Chemical Analytic Technologies).
[0093] (5) Applicable period
[0094] The pot life of the composition containing epoxy resin is measured based on the method for determining the pot life of a multi-component adhesive in JIS K6870 (method 1). In the present invention, 8.0 g of the thiol group-containing polyether polymer of each example and comparative example and 1 g of an amine compound (EHC-30 manufactured by ADEKA Corporation) are mixed with 10 g of bisphenol A type epoxy resin ("jER" 828 manufactured by Mitsubishi Chemical Co., Ltd., epoxy equivalent: 184-194) as an epoxy resin under the conditions of 23°C and 50% RH, and a toothpick is put into the epoxy resin-containing composition as the mixture, and the point at which the toothpick does not move even when touched with a finger is measured as the pot life. The pot life is measured from the start of curing, and the state of the toothpick is confirmed every 15 seconds, and is determined in minutes.
[0095] (6) Hardness
[0096] The hardness of the composition containing epoxy resin is measured by the method specified in JIS K7215. Specifically, the composition containing epoxy resin is poured into multiple containers with an inner diameter of 31 mm and a depth of 8 mm in a room at a temperature of 23°C and a humidity of 50% RH. The curing start time of the composition containing epoxy resin is taken as the starting point, and a measurement sample with a diameter of 31×thickness of 8 mm is obtained after 24 hours. The hardness of the flat surface of the sample is measured using a D-type hardness meter. The measurement is performed 3 times, and the average value is taken as the numerical value of the hardness.
[0097] (7) Tensile shear bond strength
[0098] The tensile shear bond strength of the epoxy resin-containing composition is measured according to the method specified in JIS K 6850. The specific measurement method is shown below.
[0099] Adhesive material: The surface of a 100 mm×25 mm×3 mm mild steel plate (sandblasted) was degreased using acetone and then methyl ethyl ketone to perform surface treatment.
[0100] Test piece: Prepared in a room at 23°C and 50%RH according to the dimensions specified in JIS K6850. Specifically, a composition containing epoxy resin is applied to one of two adherends, and the two adherends are bonded to each other with an overlap length of 12.5 mm and an adhesive layer thickness of about 0.2 mm. The adhesive is cured at 23°C and 50%RH, and the tensile shear bond strength is measured 24 hours after the curing start time of the composition containing epoxy resin is taken as the starting point.
[0101] Measurement method: The tensile shear bond strength was measured at a tensile speed of 2.0 mm / min using a tensile tester specified in JIS K 6850 in a room at 23°C and 50% RH. Three test pieces were used for the measurement, and the average value was taken as the tensile shear bond strength value.
[0102] [Example 1]
[0103] (Polyether polymer containing thiol group)
[0104] 250 g of trifunctional polypropylene glycol (OH value: 510 mgKOH / polypropylene glycol) obtained by adding propylene oxide to glycerol and 1.5 g of tin chloride pentahydrate were added to a 1 L reaction container, the temperature was raised to 50°C, and 248 g of epichlorohydrin (1.18 mol times the OH group of the trifunctional polypropylene glycol) was added dropwise over 1 hour. After the addition, the mixture was stirred at 80°C for 2 hours to obtain a halogen-terminated polyether polymer.
[0105] Next, the halogen-terminated polyether polymer was transferred to a sealed container, 15 g of citric acid was added, and the container was sealed. 365 g of sodium hydrogen sulfide aqueous solution (concentration 48%) was added dropwise to the sealed container, and stirred at 90° C. for 5 hours. Then, the inorganic salt and water were removed to obtain a colorless, transparent, liquid thiol-containing polyether polymer.
[0106] [-SH] / [-S] of the above-mentioned thiol group-containing polyether polymer x -] was 9.6. The content of thiol groups was 15% by mass, the viscosity at 25° C. was 4 Pa·s, the viscosity at 5° C. was 40 Pa·s, and the content of chlorine was 0.08% by mass.
[0107] (Composition containing epoxy resin)
[0108] 10.0 g of bisphenol A type epoxy resin ("jER" 828 manufactured by Mitsubishi Chemical Co., Ltd., epoxy equivalent: 184-194) as an epoxy resin, 8.0 g of the above-mentioned thiol group-containing polyether polymer as a thiol compound, and 1 g of an amine compound (EHC-30 manufactured by ADEKA Co., Ltd.) were mixed with a spatula for 60 seconds at 23°C and 50% RH to obtain a composition containing an epoxy resin.
[0109] The pot life of the epoxy resin-containing composition was 3.0 minutes. In addition, the Shore D hardness after 24 hours from the start of curing was 83, showing sufficient hardness as an adhesive. The tensile shear bond strength after 24 hours from the start of curing was 14 MPa, showing a sufficiently high value as an adhesive. The results are shown in Table 1.
[0110] [Comparative Example 1]
[0111] (Polyether polymer containing thiol group)
[0112] A commercially available thiol group-containing polyether polymer (QE-340M manufactured by Toray Fine Chemicals Co., Ltd.) was used.
[0113] [-SH] / [-S] of the above-mentioned thiol group-containing polyether polymer x -] was 5.3. The content of thiol groups was 13% by mass, the viscosity at 25° C. was 14 Pa·s, the viscosity at 5° C. was 160 Pa·s, and the content of chlorine was 0.2% by mass.
[0114] (Composition containing epoxy resin)
[0115] An epoxy resin-containing composition was obtained by carrying out the same operation as in Example 1 except that the above-mentioned thiol group-containing polyether polymer was used as the thiol compound.
[0116] Table 1 shows the evaluation results.
[0117] [Comparative Example 2]
[0118] (Polyether polymer containing thiol group)
[0119] A commercially available thiol group-containing polyether polymer (GPM-800 manufactured by Huntsman) was used.
[0120] The [-SH] / [-S x -] was 6.4. The content of thiol groups was 12% by mass, the viscosity at 25° C. was 11 Pa·s, the viscosity at 5° C. was 99 Pa·s, and the content of chlorine was 0.03% by mass.
[0121] (Composition containing epoxy resin)
[0122] An epoxy resin-containing composition was obtained by carrying out the same operation as in Example 1 except that the above-mentioned thiol group-containing polyether polymer was used as the thiol compound.
[0123] Table 1 shows the evaluation results.
[0124] Table 1
[0125]
[0126] As shown in Table 1, the [-SH] / [-S] of the thiol group-containing polyether polymer of Example 1 is x -] is as high as 7.0 or more, the viscosity is low, and the workability is excellent. On the other hand, the [-SH] / [-S] of the conventional thiol compounds of Comparative Examples 1 and 2 is x -] is less than 7.0, and the viscosity is high.
Claims
1. A thiol group-containing polyether polymer, which has a polyether portion represented by the following general formula (1) and a structural unit represented by the following general formula (2) in its main chain, and has a structural unit represented by the following general formula (3) at its terminal, and 13 In the structural analysis by CNMR measurement, the peak area corresponding to the structural unit of -SH is relative to that of -S x The ratio of the peak areas corresponding to the structural units of -[-SH] / [-S x -] is 7.0 or above; In formula (1), R 1 It is a residue obtained by removing hydrogen atoms from a polyamine or polyol having 10 or less carbon atoms, R 2 is an alkylene group having 2 to 6 carbon atoms, n is an integer of 1 to 200, and m is an integer of 2 to 8; In formula (2), S x represents one or more consecutive sulfur atoms, x is an integer from 1 to 5, and l is an integer from 0 to 10; In formula (3), l is an integer from 0 to 10. 2 . The thiol group-containing polyether polymer according to claim 1 , which contains 10 to 18% by mass of thiol groups. 3 . The thiol group-containing polyether polymer according to claim 1 , which has a viscosity at 25° C. of 0.1 Pa·s to 10 Pa·s. 4 . The thiol group-containing polyether polymer according to claim 1 , which has a viscosity at 5° C. of 1 to 70 Pa·s. 5 . An epoxy resin-containing composition comprising 100 to 600 parts by mass of the epoxy resin based on 100 parts by mass of the thiol group-containing polyether polymer according to claim 1 . 6 . The epoxy resin-containing composition according to claim 5 , wherein the composition contains 1 to 60 parts by mass of an amine based on 100 parts by mass of the epoxy resin.
7. The epoxy resin-containing composition according to claim 5 or 6, wherein 24 hours after the start of curing of the epoxy resin-containing composition, the Shore D hardness based on JIS K7215 is 70 or more, and the tensile shear bond strength based on JIS K6850 is 12 MPa or more.
8. A curing agent for epoxy resin, comprising the thiol group-containing polyether polymer according to claims 1 to 4.
Citation Information
Patent Citations
Thiol-group-containing polyether polymer and its production
JP1996269203A